Analisis Kinerja Manajemen Bank: suatu Pendekatan Balanced Scorecard (Studi pada Bank Nusa Tenggara Timur) - Man, Stanis (Universitas Brawijaya, Indonesia, 2008)
This research analyzes the application impacts from four perspectives of balanced scorecard,i.e learning and growth, internal business process, customer and financial toward total performance of bank (CAMEL). The basic thought is to raise the subject is that performance measurement of traditional management tends to stand out financial magnitude or tangible assets as a benchmark of corporation success, meanwhile measurement of management tangible assets as output performance and intangible assets as process performance. This research is aimed to examine the impacts of learning and growth performance and internal business process performance as a trigger performance toward customer performance, financial and total of bank performance as output performance in balanced Scorecard. The sampling technique used is purposive sampling. The samples in this research include 14 branch offices and 1 central office of Bank of Nusa Tenggara Timur: From the 15 offices and central office were obtained 67 respondents (bank executives from intermediate and top grades). The research data were analysed by using Partial Least Square (PLS) analysis. The descriptive analysis results indicated that Bank of Nusa Tenggara Timur performance in learning and growth perspectives and internal business process was included in respectable category, meanwhile, for consumer perspective, financial and total bank performance was included in good category. The hypothesis examination result proved that there were significant and positive influences al learning and growth and internal business process variables toward consumer performance and bank finance; however, there was no significant effect on total bank performance. Consumer variable had significant influence toward total bank performance, so did financial variable. The other specific result in this research was that consumer variable, that did not take effect toward bank financial performance.